Evacuated to Death: The Lexicon, Concept, and Practice of Mobility in the Nazi Deportation and Killing Machine. Issue 3 (3rd May 2020) - Adey, Peter
Abstract : Evacuation is a fairly empty and technical concept often used to describe moments of emergency governance when peoples are moved away from harm. It was also a key code word, though, within the Nazi deportation and killing of Europe's Jews. How could evacuation be deployed in these contexts and for these purposes? What is so crucial here is not simply that the practices of the Holocaust were termed evacuations, however inappropriate, misleading, and murderous that is, but how and why evacuation was and still is "betrayed" as a term, concept, and practice of mobility. The article interrogates evacuation's geographies and genealogies, pinpointing the Nazis' abuse of the term as a key and catastrophic, expulsive, and ultimately destructive version of evacuation mobility. The article concludes that different versions of evacuation are able to coexist and reinforce one another. Key Words: emergency, evacuation, Holocaust, mobilities, Nazi geopolitics.